Evaluation of anti-hyperlipidemia activity of Cosmos caudatus leaves in hyperlipidemic induced rat - Perumal, Vikneswari; Abdul Hamid, Azizah; Abas, Faridah; Ismail, Amin; Safinar, Intan; Shaari, Khozirah; Khatib, Alfi (2013)
Background : Hyperlipidemia is known as metabolic disorder in which the prevalence is increasing rapidly worldwide. The objective of this study was to evaluate the effectiveness of C. caudatus leaves in the treatment of hyperlipidemia in obese rats. The induced hyperlipidemic rats were given 200 mg /kg BW of C. caudatus leaves ethanolic extract and 35 mg/kg BW of atorvastatin for 4 weeks. The blood was subjected for lipid profile analysis. Results : C. caudatus for 4 weeks showed a significant (P<0.05) reduced of plasma triglyceride, total cholesterol, LDL and plasma glucose, and significantly (P<0.05) increased HDL and AI value. Conclusions : This study suggests that C. caudatus is potential for the treatment of hyperlipidemia.